2012
DOI: 10.3390/membranes2030665
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of La1−xSrxCrO3−∂ (x ~ 0.1) as Membrane for Hydrogen Production

Abstract: Various inorganic membranes have demonstrated good capability to separate hydrogen from other gases at elevated temperatures. Hydrogen-permeable, dense, mixed proton-electron conducting ceramic oxides offer superior selectivity and thermal stability, but chemically robust candidates with higher ambipolar protonic and electronic conductivity are needed. In this work, we present for the first time the results of various investigations of La1−xSrxCrO3−∂ membranes for hydrogen production. We aim in particular to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…Powders of La 0.87 Sr 0.13 CrO 3-δ were prepared by spray pyrolysis and sintered with sintering aids at 1600 1C in reducing atmospheres. For a more detailed description of the synthesis route, the reader is referred to [17]. SEM-analyses (FEI Quanta 200 F) showed that the samples had sintered dense.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Powders of La 0.87 Sr 0.13 CrO 3-δ were prepared by spray pyrolysis and sintered with sintering aids at 1600 1C in reducing atmospheres. For a more detailed description of the synthesis route, the reader is referred to [17]. SEM-analyses (FEI Quanta 200 F) showed that the samples had sintered dense.…”
Section: Methodsmentioning
confidence: 99%
“…Under reducing conditions, oxygen vacancies form and gradually take over as the major charge compensating defect [16]. Consequently, the p-type conductivity decreases to the order of 1 S cm À 1 at 1000 1C and 0.1 S cm À 1 at 300 1C in reducing atmospheres (pO 2 $ 10 -21 and $ 10 -42 , respectively) [7,17].…”
Section: Defect Transport Through a Membranementioning
confidence: 98%
See 3 more Smart Citations